Acute hemorrhagic edema of infancy (Finkelstein's disease): favorable outcome with systemic steroids in a female patient - Chávez Álvarez, Sonia; Barbosa Moreno, Laura; Ocampo Garza, Jorge; Ocampo Candiani, Jorge (2017)
Acute hemorrhagic edema of infancy was initially described in 1913 by Snow. It is a benign, self-limited leukocytoclastic vasculitis that occurs most commonly in males. It evolves favorably with conservative medical management and treatment with steroids is not usually administered.